Time function triple Langmuir probe measurements in low frequency pulsed DC discharge plasma - Farooq, M.U. (Maik Nauka Publishing / Springer SBM, 2015)
This study investigated the temporal profiles of electron temperature and number density in rectified DC air discharge generated with a 50 Hz step-up transformer. An in-house built triple Langmuir probe and circuitry were used to diagnose the plasma parameters as a function of input voltage and filling gas pressure. A tungsten metal wire capable of withstanding the high temperatures was used as probe tip material. The temporal profiles revealed an increase in electron temperature with input voltage in the range of 380 to 450 V, whereas, an inverse relation between number density and input voltage was evident in the given work. The observed trend in the plasma parameters was absolutely reversed in case of the filling gas pressure. The electron temperature linearly decreased with an increase in pressure from 1 to 4 mbar, whereas a linear increase in number density with pressure was seen in the temporal profiles. Finally, it was concluded that the results for the tested plasma parameters were consistent and the in-house built probe functioned well in DC discharge for the used range of voltage and filling pressure. Â© 2015 Pleiades Publishing, Ltd.